Long-Term Survival and Improved Quality of Life following Multiple Repeat Gamma Knife Radiosurgeries for Recurrent Glioblastoma Multiforme: A Case Report and Review of the Literature - Erik W. Larson; Halloran E. Peterson; Robert K. Fairbanks; Wayne T. Lamoreaux; Alexander R. Mackay; Jason A. Call; John J. Demakas; Barton S. Cooke; Christopher M. Lee (Case Reports in Oncological Medicine)
The management of glioblastoma multiforme (GBM) is in most cases complex and must be specifically tailored to the needs of the patient with the goals of extended survival and improved quality of life. Despite advancements in therapy, treatment outcomes remain almost universally poor. Salvage treatment options for the recurrence of the disease is an area of intense study. The following case highlights the utility of Gamma Knife Radiosurgery (GKRS) as a salvage treatment. In this clinical situation, three sequential GKRS treatments led to prolonged survival (beyond four years after diagnosis) and improved quality of life in a patient who was unable to receive further chemotherapy regimens and was unwilling to undergo further aggressive resection. To date, there have been few reports of three or more sequential GKRS treatment sessions utilized as salvage therapy for recurrent GBM in patients who can no longer tolerate chemotherapy. This report provides evidence that aggressive local treatment with GKRS at the time of recurrence may be appropriate, depending on a patient’s individual clinical situation, and can lead to prolonged survival and improved quality of life.